(4w+8)=(4w+4)=(2w+11)

Simple and best practice solution for (4w+8)=(4w+4)=(2w+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4w+8)=(4w+4)=(2w+11) equation:



(4w+8)=(4w+4)=(2w+11)
We move all terms to the left:
(4w+8)-((4w+4))=0
We get rid of parentheses
4w-((4w+4))+8=0
We calculate terms in parentheses: -((4w+4)), so:
(4w+4)
We get rid of parentheses
4w+4
Back to the equation:
-(4w+4)
We get rid of parentheses
4w-4w-4+8=0
We add all the numbers together, and all the variables
4!=0
There is no solution for this equation

See similar equations:

| 12x−8x=12 | | -82.8=5(5.5-7.3x)-0.8 | | 4t−3t=4 | | 10769/98=34/7(29/6x+9/7)-2 | | 12x=4(2x-3)-16 | | 2x+4-3x=x+8 | | z+4/9=11/9 | | 26=w/4+12 | | 609x=210x | | 854/5=7(7x-11/5) | | 3(y-5)-21=15 | | 13-9(2x+3)=4(x+8) | | -3(3-6n)=-117 | | 2(v-1)=8v+7-2(-6v-3) | | 5(3x+8)-2(4x+10)=160x | | -3(5v-2)+4v=4+2(2v-5) | | -2x+15+13x=10-5(5x-x) | | 3x-5+4x=44 | | 3x−18−8x=−2+10x+5 | | 11x+12+5x=47+7x-8 | | 14x-1+111=180 | | 10x+2+5x=-133 | | -3(5y-2)+9y=4(y+1) | | 49=8v-v | | -2+1=3x+16 | | 2x+11+5x=60 | | 16+5x=22 | | 50=-v+199 | | 18=3m+24 | | 6=12p+24 | | 76-u=279 | | 10n+1=99 |

Equations solver categories